Collaborative Strategic Leadership in Madrasahs: Integrating Islamic Governance and Distributed Leadership for Educational Quality - Ujang Suyatman; Sulhan, Moh.; Zulfa, Amanah Amnun; Hasbiyallah, Hasbiyallah; Hudin, Soleh (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
The improvement of Islamic educational quality in the contemporary era demands madrasah leadership practices that are not only adaptive and strategic but also highly collaborative in facing competitive dynamics and global institutional pressures. This study aims to analyze in depth the strategic leadership practices of madrasah principals in enhancing the quality of Islamic education by strengthening stakeholder collaboration at Madrasah Ibtidaiyah Negeri (MIN) 1 Bandung. Employing a qualitative case study design, this research explores leadership phenomena within a unique sociocultural madrasah context. Data were collected through comprehensive in-depth interviews as the primary instrument, supplemented by direct field observations and systematic documentation studies to ensure validity through data triangulation. Research participants were selected purposively, including the principal, the development team, teachers, the school committee, and parent representatives to provide a holistic perspective. The findings reveal that strategic leadership in this madrasah is developed through structured collaborative mechanisms, ranging from participatory vision and mission formulation to inclusive distribution of leadership authority and active stakeholder involvement in educational program implementation. These collaborative leadership practices have proven to significantly strengthen a participatory organizational culture, substantially increase public trust, and maintain sustainable educational quality and stability. This study underscores that collaboration-based strategic leadership is a highly effective approach to transforming the quality of Islamic education. Theoretically, this research enriches the literature on Islamic educational management, particularly regarding the application of distributed leadership practices and value-based governance in Indonesian madrasahs